A novel adaptive-fuzzy hysteresis current controller-based active power line conditioners for power quality enhancement. (1st January 2013) - Karuppanan, P.; Mahapatra, Kamala Kanta
This paper presents a three-phase shunt active power line conditioner (APLC) for harmonics and reactive power compensation to enhance the power quality. The compensation process is based on sinusoidal extraction control method, which consists of positive-sequence voltage detector to regulate the distorted supply voltage and instantaneous real-power for fundamental component extraction from the distorted line current. The voltage source inverter (VSI)-based active filter switching pulses is generated through adaptive fuzzy hysteresis current controller (HCC). For the adaptive-fuzzy-HCC, bandwidth is calculated without precise knowledge of the APLC parameters (interface inductor and DC-link voltage), the hysteresis band value can be implemented with a fuzzy logic. A comparative assessment of fixed-HCC, adaptive-HCC and adaptive-fuzzy-HCC is carried out. The shunt APLC system is validated through extensive simulation under distorted supply voltage and non-linear load conditions.